In(OTf)3 assisted synthesis of β-carboline C-3 tethered imidazo[1, 2-a]azine derivatives. (9th January 2017) - Devi, Nisha; Singh, Dharmender; Kaur, Gurpreet; Mor, Satbir; Putta, V. P. R. Kishore; Polina, Saibabu; Malakar, Chandi C.; Singh, Virender
Abstract : Synthesis of β-carboline based natural products and synthetic derivatives is one of the frontier areas of research owing to their medicinal properties. Abstract : Synthesis of β-carboline based natural products and synthetic derivatives is one of the frontier areas of research owing to their medicinal properties. It is envisaged that 3-formyl-9 H -β-carboline is a potential precursor and offers new vistas for the construction of a variety of heterocyclic architectures at the C-3 position of the β-carboline skeleton. In this context, an efficient protocol has been developed for the synthesis of β-carboline C-3 tethered imidazo[1, 2- a ]pyridine, imidazo[1, 2- a ]pyrimidine, and imidazo[1, 2- a ]pyrazine derivatives via exploration of the Groebke–Blackburn–Bienayme (GBB) reaction. The present protocol offers several advantages like operational simplicity, high atom economy, appreciable structural diversity and easy purification procedure.